2016
DOI: 10.1177/0013161x16659346
|View full text |Cite
|
Sign up to set email alerts
|

Solidifying Segregation or Promoting Diversity?

Abstract: Layered with myriad considerations, school closure and rezoning processes in urban school systems are politically fraught with the potential for damaging consequences. This article explores the politics and impacts of a closure and rezoning process in Richmond, Virginia, through the lens of themes applicable to urban school systems and students across the nation. These include the intersection of closure and rezoning with growing White reinvestment in urban school systems, as well as the importance of focusing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…The research on urban closures suggests a relatively common process of closure: state or district leaders decide that closures are necessary; they use academic and financial metrics like test scores, enrollment, or costs per pupil to select schools to close; they prepare for the closure, which can include gradually phasing out enrolled students, immediately un-enrolling students the year of the closure announcement, or shifting grade configurations in receiving schools; they close the school, usually at the end of the school year; they transition students from the closed school to an open school; and, sometimes, they sell surplus properties (Bifulco & Schwegman, 2019;Bross, Harris, & Liu, 2016;Brummet, 2014;Dowdall, 2011;Dowdall & Warner, 2013;Engberg, Gill, Zamarro, & Zimmer, 2012;Finnigan & Lavner, 2012;Jack & Sludden, 2013;Kemple, 2015;Khalifa et al, 2014;Patterson et al, 2006;Siegel-Hawley et al, 2017;Steiner, 2009;Subramaniam, 2011). The rural research, like the urban, describes the processes by which officials choose schools for closure or consolidation; generally, these decisions originate in district or state meetings and offices (Deeb-Sossa & Moreno, 2016;Patterson et al, 2006;Ward & Rink, 1992).…”
Section: Implementation Of Closurementioning
confidence: 99%
See 3 more Smart Citations
“…The research on urban closures suggests a relatively common process of closure: state or district leaders decide that closures are necessary; they use academic and financial metrics like test scores, enrollment, or costs per pupil to select schools to close; they prepare for the closure, which can include gradually phasing out enrolled students, immediately un-enrolling students the year of the closure announcement, or shifting grade configurations in receiving schools; they close the school, usually at the end of the school year; they transition students from the closed school to an open school; and, sometimes, they sell surplus properties (Bifulco & Schwegman, 2019;Bross, Harris, & Liu, 2016;Brummet, 2014;Dowdall, 2011;Dowdall & Warner, 2013;Engberg, Gill, Zamarro, & Zimmer, 2012;Finnigan & Lavner, 2012;Jack & Sludden, 2013;Kemple, 2015;Khalifa et al, 2014;Patterson et al, 2006;Siegel-Hawley et al, 2017;Steiner, 2009;Subramaniam, 2011). The rural research, like the urban, describes the processes by which officials choose schools for closure or consolidation; generally, these decisions originate in district or state meetings and offices (Deeb-Sossa & Moreno, 2016;Patterson et al, 2006;Ward & Rink, 1992).…”
Section: Implementation Of Closurementioning
confidence: 99%
“…However, residents often argue that these processes for "community input" are performative and that closure decisions are made with little regard for the immediate needs of those communities most affected (Buras, 2015;Freelon, 2018;Pappas, 2016). Most studies describing residents' reactions showed that, even with votes or forums or committees, community members felt excluded from closure and consolidation processes: They did not close their schools-instead, their schools closed on them (Alsbury & Shaw, 2005;Bard, Gardner, & Wieland, 2006;Buras, 2015;Chance & Cummins, 1998;Deeb-Sossa & Moreno, 2016;DeYoung, 1995;DeYoung & Howley, 1990;Ewing, 2018;Freelon, 2018;Gaertner & Kirshner, 2017;Kirshner, 2015;Lincove et al, 2017;Null, 2001;Patterson et al, 2006;Siegel-Hawley et al, 2017;Shiller, 2017;Vaughan & Gutierrez, 2017;. Residents sometimes felt unheard by school boards on the basis of racial discrimination (Briscoe & Khalifa, 2015;Desimone, 1993), and in other instances, residents contended that their schools were "set up" to fail by the district or state, whether due to inadequate resources for students with special education or language needs or to broader funding inequities (Freelon, 2018;Good, 2016;Kretchmar, 2014;Patterson et al, 2006).…”
Section: Implementation Of Closurementioning
confidence: 99%
See 2 more Smart Citations
“…Given this reality, community leaders have begun to organize against school closures in urban districts throughout the U.S. Concomitantly, an emerging, yet rich body of research exists on this topic. Scholars have broadly analyzed urban school closure (Deeds & Pattillo, 2014;Galletta & Ayala, 2012;Johnson, 2013;Kirshner et al, 2010), community members' influence on school closure (Finnigan & Lavner, 2012), student interpretations of school closings (Kirshner & Pozzoboni, 2011), the politics and impacts of school closure and rezoning (Siegel-Hawley et al, 2016), and the effects of school transfer after closure on students of color from low-income backgrounds (Kirshner et al, 2010). While this body of research suggests that urban school closure disrupts students' lives and neighborhoods, and is the expected outcome of neoliberal policy agendas, less research has examined how communities organize against closure to reopen schools (for exception see Buras, 2013;Good, 2016;Johnson, 2013;Lipman, 2011a;Stovall, 2007Stovall, , 2016.…”
Section: Introductionmentioning
confidence: 99%